Acute and Subacute Changes in Hip Strength and Range of Movement After Arthroscopy to Address Chondrolabral Pathology. Issue 8 (July 2019) - Freke, Matthew D.; Crossley, Kay; Sims, Kevin; Russell, Trevor; Weinrauch, Patrick; Gamboa, Gauguin; Semciw, Adam
Background: Hip pain is associated with reduced muscle strength, range of movement (ROM), and function. Hip arthroscopy is undertaken to address coexistent intra-articular pathologies with the aim of reducing pain and improving function. Purpose: To evaluate changes in strength and ROM in a cohort with chondrolabral pathology before surgery to 3 and 6 months after hip arthroscopy. Study Design: Case series; Level of evidence, 4. Methods: Sixty-seven individuals with hip pain who were scheduled for hip arthroscopy were matched with 67 healthy controls. Hip strength and ROM were collected preoperatively and at 3 and 6 months postoperatively. Repeated measures analysis of variance evaluated whether strength and ROM differed between limbs and among time points. Bonferroni post hoc tests determined differences in hip strength and ROM among testing times and between the hip pain group and matched controls. Results: Hip extension, internal rotation (IR), external rotation (ER), and adduction ( P < .040) strength were greater at 3 months after surgery; all directions, including flexion, abduction, and squeeze, were greater at 6 months ( P < .015). Hip flexion ROM was greater at 3 months after surgery ( P = .013). Flexion, IR, and ER ROM was greater at 6 months ( P < .041). At 6 months, IR ROM ( P = .003) and flexion, IR, and ER strength ( P < .005) remained less than matched controls. Conclusion: With the exception of squeeze and flexion, all directions of hip strength and hip flexion ROM are significantly improved 3 months after arthroscopy to address chondrolabral pathology. By 6 months after arthroscopy, strength in all directions and flexion and rotation ROM are significantly improved in both limbs, but hip flexion, IR, and ER strength and IR ROM remain significantly less than that of healthy matched controls in both limbs.